Awareness of age-related change in very different cultural-political contexts: A cross-cultural examination of aging in Burkina Faso and Germany - Schönstein, Anton; Schlomann, Anna; Wahl, Hans-Werner; Bärnighausen, Till (Frontiers in Psychiatry, 2023)
Combining recent developments in research on personal views on aging (VoA) and a cross-country comparative approach, this study examined awareness of age-related change (AARC) in samples from rural Burkina Faso and Germany. The aims of this study were (1) to examine for an assumed proportional shift in the relationship between gains/losses toward more losses as predicted by life span psychology; (2) to estimate the association between AARC dimensions and subjective age; and (3) to examine the association between health variables and AARC. A cross-sectional method involving a large, representative sample from rural Burkina Faso that included participants aged 40 and older (N = 3,028) and a smaller convenience sample of German respondents aged 50 years and older (N = 541) were used to address these questions. A proportional shift toward more AARC-losses was more clearly observable in the sample from Burkina Faso as compared to the German reference. In both samples, subjective age was consistently more strongly related to AARC-losses than to AARC-gains. Within the sample from Burkina Faso, differential associations of AARC-gains and AARC-losses to health variables could be shown. In conclusion, the findings support key tenets of life span psychology including that age-related gains occur even late in life and that a shift toward more losses occurs with increasing age. Also, feeling subjectively younger may indeed be more strongly guided by lowered negative aging experiences than by increased positive ones.